2021
DOI: 10.1002/fsn3.2362
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive metabolites of Blumea lacera attenuate anxiety and depression in rodents and computer‐aided model

Abstract: Blumea lacera is an edible plant with imperative medicinal values. However, the anxiolytic and antidepressant roles of B. lacera have not been well‐explained. Therefore, the current study aims to explore the impending bioactive metabolites and roles of B. lacera methanol leaf extract (Me‐BLL) in attenuating anxiety and depression through several experimental and computer‐aided approaches. The chemical characterization of Me‐BLL was performed through standard phytochemical and GC‐MS analyses. To explore the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Among them, myricetin‐3‐O‐rhamnoside and europetin‐3‐O‐rhamnoside showed antihyperglycemic activity (Küpeli Akkol et al., 2020 ; Thamilvaani Manaharan et al., 2012 ). S. campanulatum n‐hexane and methanol leaf extract contained two flavonoid compounds (2S)‐7‐hydroxy‐5‐methoxy‐6,8‐dimethyl flavanone and (S)‐5,7‐dihydroxy‐6,8‐dimethyl‐flavanone assessed in HPLC method, showing strong antiproliferative activity against human colorectal carcinoma (HCT 116) cells (Hossen et al., 2021 ; Memon et al., 2015 ). S. corticosum chloroform leaf extract contained 19 compounds.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…Among them, myricetin‐3‐O‐rhamnoside and europetin‐3‐O‐rhamnoside showed antihyperglycemic activity (Küpeli Akkol et al., 2020 ; Thamilvaani Manaharan et al., 2012 ). S. campanulatum n‐hexane and methanol leaf extract contained two flavonoid compounds (2S)‐7‐hydroxy‐5‐methoxy‐6,8‐dimethyl flavanone and (S)‐5,7‐dihydroxy‐6,8‐dimethyl‐flavanone assessed in HPLC method, showing strong antiproliferative activity against human colorectal carcinoma (HCT 116) cells (Hossen et al., 2021 ; Memon et al., 2015 ). S. corticosum chloroform leaf extract contained 19 compounds.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…Moreover, it was found that bergamot essential oil improved symptoms of stress-induced anxiety by enhancing the activities of GPx, CAT and SOD in the hippocampus and the frontal cortex [ 111 ]. Furthermore, Blumea lacera is an edible plant with various medicinal values and its leaf methanol extract mitigated anxiety-related behaviors by suppression of ROS formation via redox-related signaling pathway [ 116 ]. In a high fat diet-induced obese mouse model, low dose of alcohol decreased anxiety-like behaviors through upregulating the expression level of adiponectin and promoting the activation of Nrf2 signaling pathway [ 117 ].…”
Section: Anxietymentioning
confidence: 99%
“…Reports have shown that bioactive natural agents effectively alleviate depressive-like immobility through their anti-inflammatory, anti-oxidative, and neuroprotective effects in the experimental models (Arabi et al, 2021;Hossen et al, 2021;Hua et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%